The Efficacy of Hybrid Vaginal Ovules for Co-Delivery of Curcumin and Miconazole against Candida albicans - Brenda Maria Silva Bezerra; Sara Efigênia Dantas de Mendonça y Araújo; José de Oliveira Alves-Júnior; Bolívar Ponciano Goulart de Lima Damasceno; João Augusto Oshiro-Junior (MDPI AG, 2024)
Curcumin (CUR) is a natural compound that can be combined with miconazole (MCZ) to improve vulvovaginal candidiasis (VVC) caused by Candida albicans treatment's efficacy. This study aimed to develop ureasil-polyether (U-PEO) vaginal ovules loaded with CUR and MCZ for the treatment of VVC. Physicochemical characterization was performed by thermogravimetry (TGA), differential thermal analysis (DTA), Fourier transform infrared spectroscopy (FTIR), and in vitro release. Antifungal assays were used to determine minimum inhibitory concentrations (MICs) and synergism between CUR and MCZ, and the activity of U-PEO ovules were performed by microdilution and agar diffusion. TGA results showed high thermal stability of the hybrid ovules. In DTA, the amorphous character of U-PEO and a possible interaction between CUR and MCZ were observed. FTIR showed no chemical incompatibility between the drugs. In vitro release resulted in 80% of CUR and 95% of MCZ released within 144 h. The MICs of CUR and MCZ were 256 and 2.5 µg/mL, respectively. After combining the drugs, the MIC of MCZ decreased four-fold to 0.625 µg/mL, while that of CUR decreased eight-fold to 32 µg/mL. Synergism was confirmed by the fractional inhibitory concentration index (FICI) equal to 0.375. U-PEO alone showed no antifungal activity. U-PEO/MCZ and U-PEO/CUR/MCZ ovules showed the greatest zones of inhibition (≥18 mm). The results highlight the potential of the ovules to be administered at a lower frequency and at reduced doses compared to available formulations.